Knowledge frontiers in entrepreneurship: effectuation and bricolage - Scazziota, Vanessa Vasconcelos (2019)
Effectuation and bricolage are two alternative approaches to entrepreneurship that explain how entrepreneurs identify and explore opportunities differently from those advocated by traditional entrepreneurship models, using available resources, and actively addressing environmental constraints in order to create new businesses or markets. They are generally used to explain the entrepreneurial process in resource-scarce environments and uncertainty. Although they are approaches with significant prominence in entrepreneurship, recent literature has pointed out that some theoretical questions must be investigated in order to enhance theorization. Thus, this thesis aims to broaden the understanding of how effectuation and bricolage manifest themselves during the entrepreneurial process and the mechanisms underlying this manifestation. For this purpose, I used mixed methods, given the need to theoretically distinguish the two approaches. Study 1 is a bibliometric study that identified the knowledge base and the intellectual structure of both approaches aiming to distinguish possible points of convergence and complementarity, as required by previous works. The main contribution of this study was to integrate the approaches in an analysis that allows the understanding of how they are related and how they differ, increasing our knowledge about their frontiers. Study 2 is a meta-synthesis aiming to identify and categorize the antecedents of effectuation and bricolage, as well as to differentiate their peculiarities, responding to the calls to extend the understanding of their limits. This study also shed some light on the understanding of "how" and "when" questions about the manifestation of these approaches, which are considered to be unanswered in previous studies. Finally, Study 3 is a case study proposed to explore empirically the influence of the individual and contextual attributes identified in Study 2 and how the two approaches evolve from a dynamic perspective during the entrepreneurial process. This thesis contributes to previous research on effectuation and bricolage, developing a more general understanding of how the entrepreneurial process occurs, considering the joint analysis of the two approaches.